Improving the Ability to Dance Mokarawo Gorontalo Creative Dance Using Audiovisual Media in 4th Grade Students of SDN 1 Batudaa - Miftania Pasue; Wiwy Triyanty Pulukadang; Mimy Astuty Pulukadang; La Ode Karlan; Rustam I Husain (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study addresses the research question: